2011
DOI: 10.1177/0267659111409277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined balanced colloid and crystalloid on rotational thromboelastometry in vitro

Abstract: Our objective was to investigate the in vitro effects of a totally balanced fluid concept on whole blood coagulation. Venous blood from 12 healthy volunteers was diluted by 20% and 40% with a combination of an equal amount of colloid (balanced or unbalanced 6% HES 130/0.4, or 4% gelatin) and crystalloid (balanced or unbalanced Ringer's acetate). Blood samples were analyzed with rotational thromboelastometry (ROTEM®). The initiation of coagulation was delayed in all dilutions except for the 20 vol% gelatin-dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Data in the present report does not therefore support any clear advantage of one osmotherapeutic over the other. Nevertheless, findings in this study appear to corroborate results from two previous in vitro human studies, which demonstrated hypocoagulability caused by 15 % mannitol that was more pronounced than that caused by 2.5 % HTS or by a combination of hydroxyethyl starch with 15 % mannitol using ROTEM [ 12 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Data in the present report does not therefore support any clear advantage of one osmotherapeutic over the other. Nevertheless, findings in this study appear to corroborate results from two previous in vitro human studies, which demonstrated hypocoagulability caused by 15 % mannitol that was more pronounced than that caused by 2.5 % HTS or by a combination of hydroxyethyl starch with 15 % mannitol using ROTEM [ 12 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Gelatin colloids have been associated with hypocoagulability in humans both in vitro ( 21 , 22 ) and in vivo ( 23 ). In vitro dilution studies comparing gelatin to HES colloids have shown greater hypocoagulability with HES ( 21 , 22 , 24 ), suggesting gelatin may be the preferred colloid. The effects of gelatin colloids on coagulation in dogs have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by higher than aimed Hb levels. It has been shown before that clot strength reduces when using hydroxyethyl starch (HES)-based colloids, 21,22 and after abandoning HES solutions in surgical fluid management in the authors' institution, albumin (4% and 20% solutions) is the only choice of colloid. This in addition to the authors' patients' lack of underlying coagulation disturbances ensure proper clotting during perioperative period.…”
Section: Discussionmentioning
confidence: 99%